ทัศนคติของนักศึกษาที่มีต่อสื่อการฟัง (STUDENTS’ ATTITUDES TOWARDS LISTENING MEDIUM TYPES) - โศจิศิริกุล, พนิตพิมพ์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ สื่อจริงสำหรับการฟังได้ถูกนำมาใช้เพื่อเพิ่มความสนใจและแรงจูงใจให้นักศึกษาในการฝึกฟังภาษาอังกฤษ เพื่อสนับสนุนความคิดดังกล่าว จึงได้มีการศึกษาลักษณะของสื่อการฟังที่เป็นม้วนเทปและภาพยนตร์ เพื่อเป็นกรณีศึกษา การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อสำรวจความรู้ที่นักศึกษาได้รับจากสื่อการฟังทั้ง 2 ประเภท และทัศนคติของนักศึกษาที่มีต่อสื่อการฟังแต่ละประเภท กลุ่มตัวอย่างถูกสุ่มแบบมีเป้าหมาย ประกอบด้วยนักศึกษา จำนวน 73 คน ผู้ซึ่งลงทะเบียนเรียนวิชา LNG 101: Fundamental English I เครื่องมือที่ใช้ในการเก็บข้อมูล คือ แบบสอบถาม ผลจากการศึกษาพบว่า สื่อภาพยนตร์สามารถทำให้นักศึกษาเกิดการเรียนรู้และทัศนคติที่ดีในการฝึกฟังภาษาอังกฤษ Abstract To raise students' interest and motivation in listening lessons, authentic materials are first prioritised. To substantiate the ideas, the evidences of two listening medium types, cassettes and films, are investigated. As a case study, the research aimed to investigate what kinds of knowledge the students gained from the two types of listening media and their attitudes towards each listening medium type. The subjects selected by the purposive random sampling method were 73 students who attended LNG 101: Fundamental English I. The questionnaire was conducted for data collection. The results of the study show that films can help students learn and also create positive attitudes in studying listening.